Islamic Corporate Governance dan Pengungkapan Corporate Social Responsibility (CSR) - Shita Tiara; Debbi Chyntia Ovami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The operation of a Sharia Bank is inseparable from the demands of the implementation of Good Corporate Governance and based on Sharia principles which are referred to as Islamic Corporate Governance. This study aims to implement Islamic Corporate Governance on Corporate Social Responsibility Disclosure at BNI Syariah. This type of research in this study is qualitative. The subject in this research is BNI Syariah. The object of this research is Islamic Corporate Governance on Corporate Social Responsibility Disclosure. Data analysis techniques in this study used descriptive qualitative analysis. Achieved outcomes are journals and IPR. The results of the study show that the implementation variable of Islamic Corporate Governance has a positive influence on the disclosure of Corporate Social Responsibility (CSR) especially on BNI Syariah Jakarta Islamic Index. BNI Syariah uses 2.5% of net profit to provide Corporate Social Responsibility (CSR) funds. Disclosure of Corporate Social Responsibility (CSR) has a positive effect on the value of a company. Keywords: Islamic Corporate Governance, Corporate Social Responsibility Disclosure